Probing the hot X-ray corona around the massive spiral galaxy, NGC 6753, using deep XMM-Newton observations - Bogdán, Ákos; Springel, Volker (The astrophysical journal, 2017)
X-ray emitting gaseous coronae around massive galaxies are a basic prediction of galaxy formation models. Although the coronae around spiral galaxies offer a fundamental test of these models, observational constraints on their characteristics are still scarce. While the presence of extended hot coronae has been established around a handful of massive spiral galaxies, the short X-ray observations only allowed for measurements of the basic characteristics of the coronae. In this work, we utilize deep XMM-Newton observations of NGC 6753 to explore its extended X-ray corona in unprecedented detail. Specifically, we establish the isotropic morphology of the hot gas, suggesting that it resides in hydrostatic equilibrium. The temperature profile of the gas shows a decrease with an increasing radius: it drops from ##IMG## [http://ej.iop.org/images/0004-637X/850/1/98/apjaa9523ieqn1.gif] $kT≈ 0.7\,\mathrmkeV$ in the innermost parts to ##IMG## [http://ej.iop.org/images/0004-637X/850/1/98/apjaa9523ieqn2.gif] $kT≈ 0.4\,\mathrmkeV$ at a 50 kpc radius. The temperature map reveals the complex temperature structure of the gas. We study the metallicity distribution of the gas, which is uniform at ##IMG## [http://ej.iop.org/images/0004-637X/850/1/98/apjaa9523ieqn3.gif] $Z≈ 0.1$ Solar. This value is about an order of magnitude lower than that obtained for elliptical galaxies with similar dark matter halo mass, hinting that the hot gas in spiral galaxies predominantly originates from external gas inflows rather than from internal sources. By extrapolating the density profile of the hot gas out to the virial radius, we estimate the total gas mass and derive the total baryon mass of NGC 6753. We conclude that the baryon mass fraction is ##IMG## [http://ej.iop.org/images/0004-637X/850/1/98/apjaa9523ieqn4.gif]
Gesehen am 13.01.2021